1993
DOI: 10.1136/bmj.307.6907.759
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis and poverty.

Abstract: Objective-To examine whether the historical link between tuberculosis and poverty still exists.Design-Retrospective study examining the notifications of all forms of tuberculosis by council ward over a six year period and correlating this with four indices of poverty; council housing, free school meals, the Townsend overall deprivation index, and the Jarman index.Setting-The 33 electoral wards of the city of Liverpool.Subjects-344 residents of Liverpool with tuberculosis.Results-The rate of tuberculosis was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
108
2
17

Year Published

1995
1995
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 246 publications
(136 citation statements)
references
References 10 publications
9
108
2
17
Order By: Relevance
“…Accordingly, our reported figures do not necessarily reflect the total burden of tuberculosis carried by the inhabitants of Belleville. While there is considerable evidence pointing to the important relationship between poverty and tuberculosis mortality, 62 there has been some debate about the universality of this statement, particularly in historical populations where tuberculosis was in high general incidence 63 Our results do indicate that tuberculosis was particularly burdensome for women. Analysis revealed that a potential gain of 4.7 years would have been added to their total life expectancy after eliminating deaths due to respiratory tuberculosis (table 7).…”
Section: Respiratory Tuberculosissupporting
confidence: 34%
“…Accordingly, our reported figures do not necessarily reflect the total burden of tuberculosis carried by the inhabitants of Belleville. While there is considerable evidence pointing to the important relationship between poverty and tuberculosis mortality, 62 there has been some debate about the universality of this statement, particularly in historical populations where tuberculosis was in high general incidence 63 Our results do indicate that tuberculosis was particularly burdensome for women. Analysis revealed that a potential gain of 4.7 years would have been added to their total life expectancy after eliminating deaths due to respiratory tuberculosis (table 7).…”
Section: Respiratory Tuberculosissupporting
confidence: 34%
“…Es conocido que las condiciones materiales de vida de los grupos poblacionales y sus antecedentes seculares constituyen un importante determinante en la magnitud de esta enfermedad, tal como ocurre en los Estados Unidos (Baldó, 1966;CDC, 1992). No hay dudas de que la pobreza determina la elevación del riesgo de infección, enfermedad y de muerte por la TB, por lo que esta enfermedad tiene un fuerte componente social (Waaler, 1982;Spence, 1993). Antes de 1959, en Cuba, el 24% de la población en edad laboral estaba desempleada y unos 200 mil subempleados; alrededor del 60% de los trabajadores asalariados y por cuenta propia tenían un ingreso inferior al salario míni-mo vigente (MINSAP, 1995b); la seguridad social -insuficiente intrínsecamente -sólo protegía al 50% de los trabajadores.…”
Section: Discussionunclassified
“…It is therefore not surprising that reactivation or progression of infection with tuberculosis is sensitive to glucocorticoid therapy and to activation of the hypothalamopituitary adrenal axis. Exposing humans to the stress of war or poverty [3] or cattle to the stress of transportation are enough to cause reactivation of disease. The disease-promoting effect of stress has been demonstrated under more controlled conditions in mice [181,182].…”
Section: Adrenal Steroids In Tuberculosismentioning
confidence: 99%
“…Moreover the stresses of poverty, malnutrition and war, increase the rate of reactivation for reasons discussed later. Even in developed countries such as the United Kingdom, the disease distribution in large cities parallels the distribution of poverty [3]. Meanwhile the breakdown of healthcare systems is leading to incomplete case and contact tracing, incomplete treatment, and increases in drug resistance.…”
mentioning
confidence: 99%